2009
DOI: 10.1007/s11663-009-9247-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Nickel Product Structures Developed during the Gaseous Reduction of Solid Nickel Oxide

Abstract: The product microstructures developed during the reduction of dense synthetic nickel oxide in H 2 -N 2 and H 2 -H 2 O mixtures between 300°C and 1000°C are reported. A number of distinctly different types of nickel product structures have been identified, namely, coarse fibrous nickel with fissures, fine porous nickel-planar interface, large porous nickel-irregular interface, and dense nickel layer. The influences of gas composition and temperature on the conditions for formation of these microstructures, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…From the measurement of pore sizes, [10] it was found that the NiO reduction carried out in the present study takes place in the transition region between Knudsen and molecular diffusion. [13] In the transition region, both of the diffusion mechanisms are operative and the combined diffusivity of the Knudsen and molecular diffusions has been considered.…”
Section: Analysis Of Kinetics Of Nio Reductionmentioning
confidence: 76%
See 4 more Smart Citations
“…From the measurement of pore sizes, [10] it was found that the NiO reduction carried out in the present study takes place in the transition region between Knudsen and molecular diffusion. [13] In the transition region, both of the diffusion mechanisms are operative and the combined diffusivity of the Knudsen and molecular diffusions has been considered.…”
Section: Analysis Of Kinetics Of Nio Reductionmentioning
confidence: 76%
“…The conditions for the formation of these structures have been identified and described in a previous study. [10] In this section, an investigation of the formation mechanisms of each product is carried out by considering the formation conditions, microstructural information, and elementary processes involved.…”
Section: Formation Mechanisms Of Microstructure Developed During mentioning
confidence: 99%
See 3 more Smart Citations